Formation of professional competence of future teachers and psychologists - Yessimgaliyeva, Tlekshi M.; Zharylgassova, Peruza E.; Mugauina, Gulbaram U.; Kurmanbekova, Aigul S.; Saduakhassova, Aigul B. (Opción, 2019)
The objectives of our research is to determine the prevalence of multilingualism through surveying Kazakh students. A semi-structured interview method was used in our research. Semi-structured interviews are a part of a qualitative research methodology. As a result, the Department of Philology and Multilingual Education has an effective multilevel program for the study of the national language; a scientific and methodical system of teaching the Kazakh language has been formed on the basis of the multi-level modular technology. It can be concluded that educational psychologists in Kazakhstan are not properly educated in terms of multilingual education.